Isoniazid Preventive Therapy Completion in the Era of Differentiated HIV Care - Tram, Khai Hoan; Mwangwa, Florence; Atukunda, Mucunguzi; Owaraganise, Asiphas; Ayieko, James; Plenty, Albert; Kwariisima, Dalsone; Tamara, D. Clark; Maya, L. Petersen; Charlebois, Edwin D.; Kamya, Moses R.; Chamie, Gabriel; et al. (Journal of acquired immune deficiency syndromes, 2017)
Isoniazid preventive therapy (IPT) reduces incidence of TB by up to 60% and reduces mortality among people living with HIV (PLWH),1–4 but implementation of IPT remains poor. In East Africa, use of IPT by patients in HIV care ranges from 0.5% in Uganda to 19% in Kenya.5 Even where IPT programs are implemented, completion rates in East Africa range between 36–98%.6–11 Countries in sub-Saharan Africa are scaling up both IPT and differentiated HIV care, but there is little data to guide optimal integration of IPT into differentiated HIV care models. In differentiated HIV care stable patients typically receive quarterly ART refills either in a clinic or via community adherence groups to enhance retention in care and to decongest clinics.12,13 This less frequent scheduling is at odds with guideline recommended monthly IPT visit frequencies and could challenge successful IPT completion. To our knowledge, there are no studies assessing IPT treatment completion in the setting of well-engaged patients receiving differentiated HIV care. As such, we sought to characterize (1) baseline IPT completion rates and (2) predictors of IPT completion among HIV-infected adults, with a high rate of virologic suppression, who were receiving differentiated HIV care in 5 rural clinics in Uganda. These patients were accustomed to quarterly visits for ART refills, but to receive IPT, had to increase their visit frequency to monthly.